2011
DOI: 10.1200/jco.2010.33.7741
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Signature Classifier for Prediction of Nasopharyngeal Carcinoma Survival

Abstract: As a powerful predictor of 5-year DSS among patients with NPC, the newly developed NPC-SVM classifier based on tumor-associated biomarkers will facilitate patient counseling and individualize management of patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 37 publications
1
115
1
Order By: Relevance
“…Although the tumor-node-metastasis (TNM) staging system for NPC plays a vital role in predicting prognosis and facilitate treatment stratification, it may not be sufficiently precise (9). Beyond traditional prediction strategies, some recent studies reported that various clinical risk factors, such as hemoglobin, lactate dehydrogenase level, neutrophil-to-lymphocyte ratio, and platelet counts, were associated with poor survival (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Although the tumor-node-metastasis (TNM) staging system for NPC plays a vital role in predicting prognosis and facilitate treatment stratification, it may not be sufficiently precise (9). Beyond traditional prediction strategies, some recent studies reported that various clinical risk factors, such as hemoglobin, lactate dehydrogenase level, neutrophil-to-lymphocyte ratio, and platelet counts, were associated with poor survival (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…4 Currently, the prognosis for NPC patients is based on histological classification combined with information on the tumor size and location. 5,6 These factors are important for the detection of NPC and determining the disease stage. However, varying outcomes of clinical treatment have been reported for NPC patients with the same stage of disease treated using comparable methods.…”
mentioning
confidence: 99%
“…Second, our time period for considering patients to be free of disease may be considered short at 3 years; however, .90% of NPC relapses occur in the first 3 years after initial treatment. 20 Third, we must recognize the limitations of MRI. We can not rule out the possibility that abnormal signals in the skull base on MRI may be owing to a reactive change caused by the adjacent tumour; furthermore, slight erosions of the bone cortex may not be detectable by MRI.…”
Section: Discussionmentioning
confidence: 99%